An introduction: Fifty years later, Punishment and Social Structure in comparative analysis - Melossi, Dario (Contemporary crises, 1989)
In the same way in which Durkheim explained the invention of imprisonment on the basis of a progressive secularization and mitigation of the criminal law, or Rusche related major penological changes to social structural changes, the discussion of sociological hypotheses regarding the quantitative production of imprisonment, allows us to return to a discussion of its quality, and modalities. My hypothesis is that the ongoing deep changes in the nature of the whole arena of social control, are connected to a decreasing role of imprisonment. We certainly know very little about the size of such arena, within which a process that appears to be of increasing carceration, at least in the United States and the other "recarcerating" countries, might instead represent a shrinking section of a much faster increasing arena of social control in general.We may accept as certain only that the course set by Georg Rusche and Otto Kirchheimer fifty years ago is still wide-open today to investigation by sociologists who, like Georg Rusche, dare step beyond the role of obliging technocrats of an unquestioned legal syllogism.